Metode Guru dalam Mengajarkan Tari kepada Anak Usia Dini di RA Aisyiyah - Hilda Zahra Lubis; Nur Hasana Alvi Syahrin; Nurul Hadidah Al Hadid; Ziha Fida Utami Tanjung (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study explores the methods applied by teachers in teaching dance to early childhood children at RA Aisyiyah and its influence on their development. Dance learning does not only focus on motor skills, but also includes children's cognitive, emotional, and social growth. By implementing methods such as demonstration, imitation, imaginative play, and free exploration, teachers at RA Aisyiyah can foster creativity, discipline, and collaboration in children. This study applies a descriptive qualitative approach that takes data from observations and literature reviews. The findings show that the role of teachers is crucial as creative developers in the dance learning process, by adapting methods according to the challenges that arise, such as the child's level of focus, limited space, and variations in interests. This article highlights the importance of a combination of flexible learning methods to optimize the potential of early childhood in the fields of art and character education.